Analisis Trend dan Peramalan Nilai Tukar Nelayan (NTN) di Provinsi Aceh Tahun 2016-2035 - Apriyanty Aprianty; Melda Yulisa; Ariz Zaputra; Jainul Ubaidillah; Nasyatul Ula; Kartika Selytias Utami (Jurnal Agrisep, 2026)
This study aims to analyze the trend and forecast of the Fishermen’s Terms of Trade (Nilai Tukar Nelayan/NTN) in Aceh Province. The research used a quantitative approach with secondary time series data from Statistics Indonesia covering actual NTN values from 2016 to 2025. Trend analysis was conducted using a second-order polynomial model, while forecasting was carried out for 2026–2035. The results show that NTN in Aceh Province fluctuated during 2016–2025. NTN was below 100 in 2016, 2017, and 2020, indicating pressure on fishermen’s purchasing power. After 2020, NTN generally improved and reached its highest value in 2025. The polynomial trend model indicates a positive development pattern, suggesting a gradual improvement in fishermen’s purchasing power. This model was considered appropriate because NTN moved in a fluctuating pattern rather than following a strictly linear trend. Forecasting results show that NTN is estimated to increase from 118.72 in 2026 to 162.65 in 2035. These findings indicate potential long-term improvement in fishermen’s purchasing power. However, the forecast should be interpreted as an estimation based on historical patterns, not as a definite future value. Therefore, policies to strengthen market access, stabilize fish prices, reduce operational costs, and improve fishing facilities remain necessary to ensure that rising NTN reflects real improvements in fishermen’s welfare.